2015
DOI: 10.1002/jcb.25224
|View full text |Cite
|
Sign up to set email alerts
|

A Kinase‐Independent Function of c‐Src Mediates p130Cas Phosphorylation at the Serine‐639 Site in Pressure Overloaded Myocardium

Abstract: Early work in pressure overloaded (PO) myocardium shows that integrins mediate focal adhesion complex formation by recruiting the adaptor protein p130Cas (Cas) and nonreceptor tyrosine kinase c-Src. To explore c-Src role in Cas-associated changes during PO, we used a feline right ventricular in vivo PO model and a three-dimensional (3D) collagen-embedded adult cardiomyocyte in vitro model that utilizes a Gly-Arg-Gly-Asp-Ser (RGD) peptide for integrin stimulation. Cas showed slow electrophoretic mobility (band-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…However, p130Cas often functions via phosphorylation. There are three most common tyrosine kinase sites, Tyr165, Tyr249, and Tyr410, in the substrate domain, which play important roles in cytoskeleton remodeling, migration, and invasion 20 , 21 . We used antibodies of the phosphorylated Tyr410 site to detect the phosphorylation level of p130Cas and found that the phosphorylated p130Cas (p-p130Cas) was down-regulated in CRC cells overexpressing CSRP2, while the p-p130Cas was up-regulated in CRC cells lacking in CSRP2 (Figure 4 E; Supplementary Figure S1 D-E).…”
Section: Resultsmentioning
confidence: 99%
“…However, p130Cas often functions via phosphorylation. There are three most common tyrosine kinase sites, Tyr165, Tyr249, and Tyr410, in the substrate domain, which play important roles in cytoskeleton remodeling, migration, and invasion 20 , 21 . We used antibodies of the phosphorylated Tyr410 site to detect the phosphorylation level of p130Cas and found that the phosphorylated p130Cas (p-p130Cas) was down-regulated in CRC cells overexpressing CSRP2, while the p-p130Cas was up-regulated in CRC cells lacking in CSRP2 (Figure 4 E; Supplementary Figure S1 D-E).…”
Section: Resultsmentioning
confidence: 99%
“…Adenoviral construct for the expression of dominant negative c-Src (double mutant, K295R and Y527F) was generated using He's pAdEasy-1 system [ 13 ] as described previously [ 14 , 15 ]. Fak-CD (c-terminal domain) adenoviral construct was generously provided by Dr. William Cance’s laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Others may regulate calpain-mediated proteolytic processing of the FA protein, such as talin’s Thr114, Thr150 or Ser446 [ 176 , 177 , 178 ]. Additionally, phosphorylation events have been implicated in promoting the proper intracellular localization of the protein, as is the case with phosphorylation of Ser139, Ser437, or Ser639 on p130Cas [ 184 ]. There are also quite a few defined phosphorylation sites which help modulate relief from autoinhibitory configurations.…”
Section: Multiple Regulatory Mechanisms Control Focal Adhesion Dynmentioning
confidence: 99%